2022
DOI: 10.1136/bmjoq-2022-001911
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and narrative synthesis of the impact of Appreciative Inquiry in healthcare

Abstract: BackgroundAppreciative Inquiry is a motivational, organisational change intervention, which can be used to improve the quality and safety of healthcare. It encourages organisations to focus on the positive and investigate the best of ‘what is’ before thinking of ‘what might be’, deciding ‘what should be’ and experiencing ‘what can be’. Its effects in healthcare are poorly understood. This review seeks to evaluate whether Appreciative Inquiry can improve healthcare.MethodsMajor electronic databases and grey lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Appreciative Inquiry was chosen to guide the initial activities as it allows for the engagement of the hearts, souls, and minds of people engaged in creating change using four stages: (1) discovery, (2) dream, (3) design, and (4) destiny (Copperfield & Whitney, 2005;Cowling, 2001Cowling, , 2004Cowling, , 2023Cowling & Repede, 2010;Merriel et al, 2022;Verheijen et al, 2020). In the first stage (discovery), the topic selection is based on related concerns or issues, what the group wants to discover, and a deep dive into the literature.…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Appreciative Inquiry was chosen to guide the initial activities as it allows for the engagement of the hearts, souls, and minds of people engaged in creating change using four stages: (1) discovery, (2) dream, (3) design, and (4) destiny (Copperfield & Whitney, 2005;Cowling, 2001Cowling, , 2004Cowling, , 2023Cowling & Repede, 2010;Merriel et al, 2022;Verheijen et al, 2020). In the first stage (discovery), the topic selection is based on related concerns or issues, what the group wants to discover, and a deep dive into the literature.…”
Section: Designmentioning
confidence: 99%
“…Appreciative Inquiry is used in both nursing and organizational research to frame quantitative and qualitative studies (Cowling, 2004; Merriel et al, 2022). Using appreciative inquiry in a qualitative study of women in despair, Cowling (2004) described the process he used to provide a listening space for their stories to be told.…”
Section: Designmentioning
confidence: 99%
“…This approach is complementary to the prevailing approach to improvement which tends to focus on understanding failure. A recent systematic review identified a lack of high-quality empirical evidence to support the effectiveness of AI to inform positive change in the quality and safety of healthcare, 10 so we intend the results of this study to build on the research in this area.…”
Section: Introductionmentioning
confidence: 99%
“…A potential method to create this culture is appreciative inquiry which is becoming increasingly embedded within healthcare and more specifically around learning to improve the quality and safety of healthcare (Beaumont, 2017; Crust, 2023; Merriel et al, 2022). It can effect positive change in complex, human-based systems.…”
mentioning
confidence: 99%